Dampak Monopoli Avtur Terhadap Persaingan Usaha: Kajian Hukum dan Kebijakan Studi Kasus PT X - Charla Vilia Aprilly; Citra Fathimah; Dahlia Istiqomah; Eka Amalia Romadhoni; Rendy Oktavianada (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
In business activities, it is inevitable that there will be competition among business actors. The emergence of a problem in business competition is a form of imbalance in the market. KPPU as a supervisory institution has an important role in enforcing regulations related to business competition. This research focuses on a case study of PT X as a suspected company that commits monopolistic practices in the supply of avtur in Indonesia. This research aims to examine the impact of aviation fuel monopoly by PT X on business competition in the Indonesian aviation industry, with a focus on legal and policy aspects. This research uses a qualitative method with a case study type through a descriptive approach. This method was chosen because it is suitable for exploring regulations in depth as well as existing social phenomena to be able to reveal the understanding of various parties involved. The results showed that PT X is suspected of violating Law No.5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, especially Article 17 which prohibits monopolistic practices, violation of Article 19 letter a and or d (market control) of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, and violation of BPH Migas Regulation No.13/P/BPH Migas/IV/2008 on the Regulation and Supervision of the Implementation of the Supply and Distribution of Aviation Fuel Oil at Airports. Based on these preliminary findings, KPPU has increased the status of the investigation to the formal investigation stage and plans to summon several related parties for further questioning. The impact caused by the monopoly by PT X is that it creates unfair business competition because other companies find it difficult to compete because they cannot compete effectively.